Bukit Hijau Enterprise "Desa Permai Homestay Resort" / Mohamad Farid Othman ... [et al.] - Othman, Mohamad Farid; Ahmad, Mas Azmimin; Mohd Yusof, Mohd Fareed; Rasid, Mohd Rasidee; Jaafar, Mohd Fairos (2003)
Desa Permai Homestay Resort, which wholly owned by Bukit Hijau Enterprise, is specialized on services business based on recreation and tourism. We run a partnership business that is contributed by Mohd. Fairos B. Dato' Jaafar as a General Manager, Mohd Fareed B. Hj. Mohd Yusof as a Administration Manager, Mas Azmimin B. Ahmad as a Marketing Manager, Mohd Rassidee B. Mohd Rasid as a Operation Manager, and Mohamad Farid B. Othman as a Financial Manager. General Manager contributes RM 48843 while the other managers contribute RM36343 each one. So the total contribution from every partner is RM 194215 as a capital to the business and Bank Bumiputera Commerce finances the balance. The entire partner has good academic qualification, have working experiences and the most important thing is all the partners are skillful in their own field. We also have a clerk to help us in run the administration management at the office while under the operation manager, there are 4 workers; 2 gardeners and 2 housekeepers to help operation activities in the resort. Our business is located at Lot 2233, Kg. Sg. Badak, Mukim Gurun, 08600 Kuala Muda, Kedah Darul Aman. We choose this place because it is very comfortable to the people who want to get the privacy and a peaceful environment on their holiday. There are also other facilities that we provide to the customer in the resort. As a conclusion, all the partners will run the business, as a one team who will work and cooperate together to achieve our goal for the company.